1996
DOI: 10.1088/0022-3727/29/4/022
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the absolute fluorescence quantum yield of rhodamine B solution using a dual-beam thermal lens technique

Abstract: The dual-beam thermal lens technique has been found to be very effective for the measurement of fluorescence quantum yields of dye solutions. The concentration-dependence of the quantum yield of rhodamine B in methanol is studied here using this technique. The observed results are in line with the conclusion that the reduction in the quantum yield in the quenching region is essentially due to the non-radiative relaxation of the absorbed energy. The thermal lens has been found to become abberated above 40 mW of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 15 publications
(11 reference statements)
3
39
0
Order By: Relevance
“…Details of the experimental set up used for the cw thermal lens 7 and pulsed thermal lens 8 are given elsewhere. For a transient thermal lens, 532 nm radiation from a frequency-doubled Qswitched Nd:YAG laser (FWHM 9 ns) was used as the pump source to generate a thermal lens in the medium.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the experimental set up used for the cw thermal lens 7 and pulsed thermal lens 8 are given elsewhere. For a transient thermal lens, 532 nm radiation from a frequency-doubled Qswitched Nd:YAG laser (FWHM 9 ns) was used as the pump source to generate a thermal lens in the medium.…”
Section: Methodsmentioning
confidence: 99%
“…F u and F s are the integral intensity, A U and A s stand for absorption values, n u and n s denote the refractive indexes of the solvents, and subscripts u and s refer to the samples and standard substance, respectively. The fluorescence quantum yield of RhB is 0.82 [26] . 1.2.4 The fluorescence spectrum and RRS spectrum of the combination formed by reaction of CdTe nanocrystals with aminoglycoside antibiotics.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…As a comparison, for Rhodamine B dye dissolved in methanol, the  values decreased from 0.8 to ~0.1 with increasing concentration in the range of ~10 -5 -10 -3 molar (Bindhu et al, 1996). For CdSe/ZnSe core/shell nanocrystals suspended in organic solvents, the values of = (0.60-0.85) were obtained, as a result of the thicker deposit shell concentration (Reiss et al, 2002); quantum yield values were reported as 0.4-0.6 for CdSe QDs (core-sizes between 2.8 and 5.0 nm), 0.55 for CdSe/ZnSe/ZnS (Donegá et al, 2006) and up to 0.70 for CdTe/CdS MSNs aqueous colloidal solution (Deng et al, 2010).…”
Section: Wwwintechopencommentioning
confidence: 95%